Ecosystem services as public goods in the function of tourism in Croatian national parks - Pavlinović Mršić, Slađana (Oeconomica Jadertina, 2026)
Protected areas can represent an important component of the tourism product, and through tourism, the economic role of protected areas can be observed through tourism. However, national parks represent original parts of nature, and the economic use of their resources is prohibited. Therefore, the purpose of this paper is to review and understand the justification for this form of protection of natural values ​​by analyzing the tourism significance of ecosystem services in Croatian national parks. The aim of the paper is to demonstrate the economic role of ecosystem services in protected areas using examples of tourism activities. Starting from the definition of public goods and the ecosystem approach, ecosystem services used in tourism in Croatian national parks are compared. For the purposes of the paper, secondary data available in the management plans of selected protected areas on ecosystem services related to tourism were analysed and compared in detail. The CICES classification was applied to identify and compare the aforementioned services, which are then viewed in relation to the type of good from the aspect of rivalry and exclusivity, which contributes to understanding the problems of managing such goods. Eight classes of cultural services that can be associated with tourism activities in the considered national parks were identified, such as recreational activities, enjoyment of the landscape, resonance with the cultural heritage of the area, as well as additional classes such as the use of visual materials, erosion control, and wind protection. The results of the analysis of the rivalry and exclusivity of the identified ecosystem services indicate the importance of managing tourism activities in the observed national parks.
Keywords: protected areas, ecosystem services, CICES, public good problem, economic valuation of the environment